Social Media Usage and Agricultural Extension Service Delivery. Implications for Effectiveness in Northwest Nigeria - Alhassan, Y. J.; Muhammad, A. M.; Chari, A. D. (Discoveries in Agriculture and Food Sciences, 2022)
Social media are tools meant for digital communication that aids in the interaction among a group of people and acts as information exchange media across the globe. Since ages newspapers, television, and magazines have been the most used source of information in the agriculture sector. But now the power of the 21st century is literally in our hands. Platforms like Facebook, YouTube, and Whatsapp have 2.6 billion, 2 billion, and 1.6 billion active monthly users respectively as of 2020 (Anonymous1 2020). Agricultural extension agents use social media to access information needed to improve their agricultural service delivery in northwest Nigeria. The broad objective of this study is to assess the implications of social media usage in Agricultural Extension Service Delivery in Northwest Nigeria. Other specific objectives were to ascertain the areas where social media has helped extension agents in engaging youths in agriculture; find out the socioeconomic factors that influences usage of social media for agricultural information transmission. A sample of three hundred and sixty youths in agriculture was randomly selected through the multi-stage sampling techniques in the study area. The instruments used for data collection were questionnaire and focus group discussion. The theories of Utility and Rational served as theoretical framework for the study. The data was analyzed using descriptive statistics and logit regression model. Data were analysed using Statistical Packages for Social Science (SPSS). The null hypotheses that guided this study is socio- economic factors do not significantly influence the usage of social media by agricultural extension agents to engage youth in agriculture in the study area. Results of the logit regression analysis carried out to establish the social-economic factors that significantly influence the usage of social media by extension agents to train youth in agriculture showed that the independent variables studied accounted for a coefficient of multiple determination of 0.510 (51.0%). Out of all the socioeconomic factors that influenced usage of social media in agriculture only age (0.994), education (0.642), farm experience (-0.158), income (.000) and sex (1.768) were found to significantly influence the usage of social media in agriculture. Findings revealed that most of the respondents (30.0%) indicated that extension agents used social media to engage youths in agriculture through extension services. These findings recommended the need of the useful of these variables in the usage of social media in agriculture.